Bomberger, Mrs. F. J. (Emma) (Faribault County Historical Society, 405 East 6th Street, Blue Earth, Minnesota)
35fd4c11d812bd49d948969ed5f822ac
United States
Minnesota
Faribault
Blue Earth
35fd4c11d812bd49d948969ed5f822ac
Keywords: Teacher, Grade 1,1890 -1894; Blue Earth School; Bomberger, Emma (Mrs. F. J.); Education